Tingkat Produksi Ratun berdasarkan Tinggi Pemotongan Batang Padi Sawah Saat Panen - Susilawati , (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
The objectives of the study was to determine the effect of cutting height of main crop on the yield of rice ratoon, and toselect genotypes with high productivity on tidal swamp land. The method used was a factorial randomized block design withthree replications. The first factor was cutting height of 10 cm, 20 cm and 30 cm from soil surface. The second factor was fivegenotypes selected from previous study, namely Cimelati, Hipa-5, Rokan, IPB106-7-47-DJ-1 and IPB106-F-8-1. The resultsshowed that combination of genotypes and cutting height affected ratoon yield. Cutting height of 20 cm increased the numberof filled grain in almost all genotypes, increased growth rate of ratoon to 1.5 cm day-1 and increased growth uniformity ofratoon of Cimelati, Hipa-5 and Rokan geontypes, with production 3.0 ton ha-1, 2.8 ton ha-1 and 2.2 ton ha-1, equal with 57.2%,60.1%, 52.7%, of the main crop respectively. Cutting height of 10 cm above soil surface showed the best results for IPB106-7-47-DJ-1 and IPB106-F-8-1 genotypes, with the highest yield of ratoon 2.1 ton ha-1 and 1.5 ton ha-1, equal with 45.8% and35.4% of the main crop respectively.Keywords: cutting height, ratoon, yield